Peran Program Nasional Pemberdayaan Masyarakat (PNPM) Mandiri Dalam Mengatasi Kemiskinan - Hasan Jan, Radlyah; Hasan, Faradila; Janis, Budi (ARBITRASE: Journal of Economics and Accounting, 2023)
The problem of poverty is an issue that has existed for a long time and it can almost be said that it will remain an "eternal fact" in life. The definition of poverty itself as a scientific concept was born as a side effect of the term development. Hence, in every discussion about development, the discussion about development, especially the discussion of poverty, gets an important place. Poverty is seen as part of the problem in development, whose existence is marked by unemployment, underdevelopment which then increases into inequality. In this case, this study aims to look for the role of PNPM Mandiri in overcoming community poverty in Islamic urban villages. In addition, this study also examines the impact of PNPM Mandiri on the community in overcoming poverty. Methodologically, this study employed a qualitative method using an analytical descriptive approach. In the meantime, data collection was carried out using three methods, namely in-depth interviews, observations of the processes or results of PNPM Mandiri activities, as well as the collection of relevant documents. In general, this study found that the PNPM Mandiri program in Islamic Kelurahan had been implemented properly. The program implemented included the distribution of revolving funds. Only a portion of the fund disbursement program was actually utilized by the poor. Regarding PNPM Mandiri for overcoming poverty, PNPM Mandiri activities in the form of channeling revolving funds were still not helping the community's economy, because the funds disbursed were small in number while the community's need for business capital was large. For this reason, it had not been able to provide fundamental changes in society.